Nitrogen-containing branched polymer, anion exchange resin, anion exchange membrane, and electrochemical device
By using nitrogen-containing branched polymer and quaternization treatment, the trade-off effect between ion conductivity, structural stability and water absorption swelling characteristics in the anion exchange membrane is solved, and an efficient and stable anion exchange membrane is achieved, which improves the Safety and performance of electrochemical devices.
Patent Information
- Application Number
- CN202411262014.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-07
AI Technical Summary
While improving the ion conductivity, the existing anion exchange membrane has a trade-off effect between structural stability and water absorption swelling characteristics, resulting in a decrease in mechanical properties and safety hazards.
A nitrogen-containing branched polymer was used as the backbone, and anion exchange resin and film with high ionic conductivity and low water absorption swelling were prepared through specific molar proportion and polydispersion index control, combined with quaternization treatment.
The high ionic conductivity, structural stability and low water absorption swelling characteristics of the anion exchange membrane are achieved, and the safety and electrochemical performance of the electrochemical device are improved.
Smart Images

Figure CN119264352A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of anion exchange membranes, and in particular, relates to a nitrogen-containing branched polymer, anion exchange resin, anion exchange membrane and an electrochemical device. Background Art
[0002] The trade-off effect, also known as the trade-off effect, usually refers to a situation where a trade-off is made between two or more parameters. The trade-off effect indicates that for the same product, when a priority is given to one performance, another performance may be compromised, and vice versa. In the field of materials, the existence of the trade-off effect poses an obstacle to the promotion and application of new materials.
[0003] Anion exchange membranes (AEMs) are the core components of alkaline electrochemical devices. Their function is to conduct OH- from the cathode to the anode of the electrochemical device, and at the same time, they can block the direct transfer of gas and electrons between the electrodes. The key properties of AEMs related to alkaline electrochemical devices are high ion conductivity, low swelling, high mechanical strength and excellent alkaline stability.
[0004] When developing ideal AEMs for alkaline electrochemical devices, the polymer backbone and cationic groups of AEMs are important design considerations. At present, the strategy of combining a polyaromatic backbone without aromatic ether as the polymer backbone of AEMs with a nitrogen-containing heterocyclic ring as the cationic group of AEMs is generally adopted to improve the durability of AEMs. However, the trade-off effect between ionic conductivity and structural stability is still the main problem faced by most AEMs. Sufficient conductive groups are required to ensure the high ionic conductivity of AEMs, but the introduction of conductive groups will inevitably lead to reduced structural stability and mechanical properties of membrane materials. In order to achieve the improvement of the mechanical stability of AMEs membrane materials, the cross-linking method can be used to improve it, but the cross-linking operation will greatly reduce the ionic conductivity of AMEs, and also reduce the toughness of the membrane to a certain extent, making the membrane brittle. On the other hand, there is also a trade-off effect between ionic conductivity and water absorption and swelling properties. AEMs often have high water absorption and swelling properties while achieving high ionic conductivity. Generally speaking, the greater the water swelling of AEMs, the richer and wider their corresponding hydration channels, which will lead to increased hydrogen transmembrane permeation in practical applications, posing a major safety hazard.
[0005] In summary, in the process of improving and developing AEMs, trade-off effects are common between different performance indicators, which seriously limits the industrialization of AEMs of this type of material system. Summary of the invention
[0006] In order to alleviate the trade-off effect between the ionic conductivity, structural stability and water absorption and swelling characteristics of AEMs, so that the ionic conductivity of AEMs is improved, the structural stability is enhanced, and the water absorption and swelling rate is reduced, the present invention provides a nitrogen-containing branched polymer, anion exchange resin, anion exchange membrane and electrochemical device.
[0007] According to a first aspect of the present invention, a nitrogen-containing branched polymer is provided, wherein the molecular structure of the nitrogen-containing branched polymer comprises a nitrogen-containing heterocycle, a branching structure and a biphenyl group, the number of branching points of each branching structure is not less than 3, and the biphenyl group is connected to the branching site of the branching structure through the nitrogen-containing heterocycle; A represents the molar proportion of the biphenyl group in the nitrogen-containing branched polymer, and B represents the molar proportion of the branching structure in the nitrogen-containing branched polymer, A:B=80-99:1-20; the polydispersity index PDI of the nitrogen-containing branched polymer is ≤2.6, and the weight average molecular weight of the nitrogen-containing branched polymer is 40000 g / mol to 500000 g / mol. By making the content of biphenyl group and branched structure in polymer within a specific ratio range, the basic skeleton of nitrogen-containing polymer has good structural strength and contains rich conductive groups. Based on the above skeleton structure, the weight average molecular weight and polydispersity index PDI of the polymer are further controlled within a certain range, so that the structural strength of the nitrogen-containing branched polymer is further improved, and the corresponding water absorption swelling rate is controlled at a lower level. Based on this, the trade-off effect between the ionic conductivity, structural stability and water absorption swelling characteristics of the nitrogen-containing branched polymer is alleviated. The nitrogen-containing branched polymer provided by the present invention can have excellent example conductivity and mechanical properties under the premise of achieving a low level of water absorption swelling rate, and is suitable for preparing efficient and stable anion exchange resins and anion exchange membranes.
[0008] Preferably, A represents the molar proportion of the biphenyl group in the nitrogen-containing branched polymer, and B represents the molar proportion of the branched structure in the nitrogen-containing branched polymer, and A:B=85-95:5-15.
[0009] Preferably, the biphenyl group includes at least one of a diphenyl group, a terphenyl group, and a quaterphenyl group.
[0010] Preferably, the branched structure includes a benzene ring structure provided with branching sites.
[0011] Preferably, the branched structure includes at least one of the following structures: 1,3,5-triphenylbenzene structural unit, triphenylmethane structural unit, 9,10-triphenylene structural unit, tetraphenylmethane structural unit, triptycene structural unit, 9,9'-diphenylfluorene structural unit, 9,9'-spirobifluorene structural unit, 9,9'-bifluorene structural unit, 9,9'-bicarbazole structural unit, 4,4-di(9-carbazole)biphenyl structural unit, 2,2'-bi-9,9'-spirobi[9H-fluorene] structural unit, triphenylamine structural unit.
[0012] Preferably, the nitrogen-containing heterocyclic ring includes at least one of a piperidine ring and a quinuclidine ring.
[0013] Preferably, the molecular structure of the nitrogen-containing branched polymer includes segment I and segment II; the general structural formula of segment I is Wherein, A represents a nitrogen-containing heterocycle, Ar1 represents a biphenyl group, and X represents the degree of polymerization of segment I; segment II is composed of a nitrogen-containing heterocycle and a branched structure, and in segment II, the nitrogen-containing heterocycle is directly connected to the branching site of the branched structure.
[0014] Preferably, the nitrogen-containing branched polymer comprises a basic structural unit formed by connecting segment I and segment II; in the basic structural unit, segment I and segment II are connected in the manner that the biphenyl group in segment I connects the nitrogen-containing heterocycle in segment II.
[0015] Preferably, in the basic structural unit, the number of segments I directly connected to each segment II is ≥3.
[0016] Preferably, the weight average molecular weight of the nitrogen-containing branched polymer is 40,000 g / mol to 250,000 g / mol.
[0017] Preferably, the weight average molecular weight of the nitrogen-containing branched polymer is 40,000 g / mol to 130,000 g / mol.
[0018] Preferably, the biphenyl group is a terphenyl group.
[0019] Preferably, the biphenyl group is p-terphenyl group.
[0020] Preferably, the nitrogen-containing polymer comprises at least one of nitrogen-containing branched polymer A, nitrogen-containing branched polymer B, nitrogen-containing branched polymer C, nitrogen-containing branched polymer D, and nitrogen-containing branched polymer E; the nitrogen-containing branched polymer A is
[0021]
[0022] The nitrogen-containing branched polymer B is
[0023]
[0024] The nitrogen-containing branched polymer C is
[0025]
[0026] The nitrogen-containing branched polymer D is
[0027]
[0028] The nitrogen-containing branched polymer E is
[0029]
[0030] According to a second aspect of the present invention, a method for preparing the above nitrogen-containing branched polymer is provided, comprising the following operations: S1. preparing a reaction monomer mixture containing monomer I, monomer II, and monomer III, wherein monomer I is a biphenyl monomer, monomer II is a monomer including a branched structure, and monomer III is a monomer including a nitrogen-containing heterocycle, and adding an acid catalyst to the reaction monomer mixture under a temperature condition of -5°C to 0°C to obtain a reaction solution; S2. allowing the reaction solution to undergo an oligomerization reaction, the reaction temperature of the oligomerization reaction is 0°C to 10°C, and an oligomer mixture is obtained after the oligomerization reaction is completed; S3. allowing the oligomer mixture to undergo a polymerization reaction, the reaction temperature of the polymerization reaction is 0°C to 24°C; S4. separating a polymer from the product after the polymerization reaction is completed, and performing a deacidification treatment on the polymer, and the polymer is converted into a nitrogen-containing branched polymer after the deacidification treatment.
[0031] Preferably, in S1, the acid catalyst is added to the reaction monomer mixture in a dropwise manner, and the dropwise addition speed is 0.3 mL / min to 2 mL / min.
[0032] Preferably, the reaction time of the oligomerization reaction is 1 to 5 hours, and the reaction time of the polymerization reaction is 1 to 15 hours.
[0033] Preferably, in S4, the polymer is discharged through an extruder into a columnar extrudate, and the radial cross-sectional diameter of the extrudate is 0.5 mm to 2.5 mm.
[0034] Preferably, in S4, the extrudate is discharged into pure water or an aqueous solution, wherein the solute in the aqueous solution comprises at least one of potassium carbonate, sodium carbonate, sodium chloride, potassium hydroxide and calcium chloride.
[0035] According to a third aspect of the present invention, an anion exchange resin is provided, the anion dendron exchange resin comprising a quaternary ammonium product of the nitrogen-containing branched polymer as described above. The anion exchange resin can have excellent ionic conductivity and mechanical properties while achieving low water absorption and swelling, and can be used to prepare an efficient and stable anion exchange membrane.
[0036] Preferably, the anion exchange resin includes at least one of anion exchange resin A, anion exchange resin B, anion exchange resin C, anion exchange resin D, anion exchange resin E, anion exchange resin F, anion exchange resin G, anion exchange resin H, anion exchange resin I, anion exchange resin J, anion exchange resin K, and anion exchange resin L;
[0037] Anion exchange resin A is
[0038]
[0039] Anion exchange resin B is
[0040]
[0041] Anion exchange resin C is
[0042]
[0043] Anion exchange resin D is
[0044] Anion exchange resin E is
[0045]
[0046] Anion exchange resin F is
[0047]
[0048] Anion exchange resin G is
[0049]
[0050] Anion exchange resin H is
[0051]
[0052] Anion exchange resin I is
[0053]
[0054] Anion exchange resin J is
[0055]
[0056] Anion exchange resin K is
[0057]
[0058] Anion exchange resin L is
[0059]
[0060] Preferably, the anion exchange resin includes at least one of anion exchange resin A, anion exchange resin B, anion exchange resin C, anion exchange resin D, and anion exchange resin E.
[0061] According to a fourth aspect of the present invention, a method for preparing the anion exchange resin as described above is provided, comprising the following operations: S1. preparing a reaction monomer mixture containing monomer I, monomer II, and monomer III, wherein monomer I is a biphenyl monomer, monomer II is a monomer including a branched structure, and monomer III is a monomer including a nitrogen-containing heterocyclic ring, and adding an acid catalyst to the reaction monomer mixture at a temperature of -5°C to 0°C to obtain a reaction solution; S2. allowing the reaction solution to undergo an oligomerization reaction, wherein the reaction temperature of the oligomerization reaction is 0°C to 10°C, and the oligomerization reaction structure is After the polymerization, a mixed oligomer solution is obtained; S3. The mixed oligomer solution is polymerized at a reaction temperature of 0°C to 24°C; S4. A polymer is separated from the product after the polymerization reaction, and the polymer is subjected to an acid removal treatment, and the polymer is converted into a nitrogen-containing branched polymer after the acid removal treatment; S5. The nitrogen-containing branched polymer and a quaternary ammonium agent are added to solvent B to prepare a quaternary ammonium reaction solution, and then the nitrogen-containing branched polymer and the quaternary ammonium agent are subjected to a quaternary ammonium reaction, and an anion exchange resin is separated from the product obtained by the quaternary ammonium reaction.
[0062] The anion exchange resin is prepared by the above method, which can effectively improve the problem of molecular weight heterogeneity faced by branched materials when the degree of branching is further increased, and the anion exchange resin of the present invention can be prepared in a controllable and stable manner. In addition, the solubility of highly branched materials is effectively improved, thereby ensuring the excellent performance of anion exchange resins containing branched structures.
[0063] Preferably, in S1, the acid catalyst is added to the reaction monomer mixture in a dropwise manner, and the dropwise addition speed is 0.3 mL / min to 2 mL / min.
[0064] Preferably, the reaction time of the oligomerization reaction is 1 to 5 hours, and the reaction time of the polymerization reaction is 1 to 15 hours.
[0065] Preferably, monomer I comprises at least one of the following biphenyl monomers:
[0066]
[0067] Preferably, monomer II comprises at least one of the following materials:
[0068]
[0069]
[0070] Preferably, monomer III includes at least one of a piperidone monomer and a quinuclidinone monomer.
[0071] Preferably, the piperidone monomer has the general structural formula Wherein, R1 and R2 are independently selected from methyl, ethyl, propyl, butyl, pentyl, cyclopropyl, and cyclopropyl.
[0072] Preferably, the general structural formula of the quinuclidinone monomer is Wherein, R3 is hydrogen, alkyl, alkenyl, alkynyl or aromatic ring.
[0073] Preferably, the piperidone monomer comprises at least one of the following materials,
[0074]
[0075] The nicotinamide monomer comprises at least one of the following materials:
[0076]
[0077] Preferably, the acid catalyst includes at least one of methanesulfonic acid, pentafluoropropionic acid, trifluoroacetic acid, trifluoromethanesulfonic acid, and heptafluorobutyric acid. Taking the feeding amount of monomer III as an equivalent reference, the feeding amount of the acid catalyst satisfies 4eq to 14eq.
[0078] Preferably, the acid catalyst includes trifluoroacetic acid and trifluoromethanesulfonic acid.
[0079] Preferably, taking the feeding amount of monomer III as an equivalent reference, the feeding amounts of trifluoroacetic acid and trifluoromethanesulfonic acid satisfy trifluoroacetic acid:trifluoromethanesulfonic acid=0.5eq-3eq:3.5eq-11eq.
[0080] Preferably, in the above S5, the feeding amounts of the nitrogen-containing branched polymer and the quaternary ammonium agent are calculated in molar ratio to satisfy the following ratio: nitrogen-containing branched polymer: quaternary ammonium agent = 1: (1 to 3)
[0081] Preferably, the quaternizing agent comprises at least one of methyl trifluoroacetate, methyl p-toluenesulfonate, iodomethane, propyl bromide, ethyl iodide, propyl iodide, butyl iodide, pentyl iodide, hexyl iodide, ethyl bromide, butyl bromide, pentyl bromide, hexyl bromide, cyclohexyl bromide, cyclopentyl bromide, cyclohexyl bromide, methyl methanesulfonate, ethyl methanesulfonate, propyl methanesulfonate, butyl methanesulfonate, propyl ethanesulfonate, ethyl ethanesulfonate, but-3-yn-1-yl methanesulfonate, allyl allylsulfonate, methyl benzenesulfonate, methyl nitrobenzenesulfonate, methyl trifluoromethanesulfonate, ethyl trifluoromethanesulfonate, ethyl toluenesulfonate, cyclobutyl toluene-4-sulfonate, butyl toluenesulfonate, neopentylbenzenesulfonate, tetrahydro-2H-pyran-4-yl methanesulfonate, or cyclohexyl p-toluenesulfonate.
[0082] Preferably, preparing the reaction monomer mixture comprises the following operations: mixing monomer I, monomer II and monomer III in solvent A, wherein solvent A is composed of at least one of dichloromethane, chloroform, chloroform or tetrahydrofuran.
[0083] Preferably, the reaction temperature of the quaternization reaction is 10°C to 100°C.
[0084] Preferably, the reaction time of the quaternization reaction is 4 hours to 36 hours.
[0085] Preferably, solvent B is composed of at least one of dimethyl sulfoxide, tetrahydrofuran, N-methyl-2-pyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide, and acetonitrile.
[0086] Preferably, in S5, separating the anion exchange resin from the product obtained by the quaternization reaction specifically comprises the following operations: adding a precipitant to the product obtained by the quaternization reaction, washing and drying the precipitate precipitated from the product, and then subjecting the precipitant to ion exchange treatment to obtain the anion exchange resin; the precipitant comprises at least one of ethanol, ethyl acetate, ethylene glycol, ether, tetrahydrofuran, acetone or water.
[0087] According to a fifth aspect of the present invention, an anion exchange membrane is provided, the anion exchange membrane comprising the anion exchange resin as described above. The anion exchange membrane provided by the present invention not only has good mechanical properties but also can achieve high ion conductivity. When applied to an electrochemical device, the electrochemical performance and structural stability of the electrochemical device can be significantly improved. In addition, since the anion exchange membrane has a low water absorption swelling rate, the volume of its hydration channel can be reduced, thereby maintaining a low hydrogen transmembrane permeability in the electrochemical device using it.
[0088] According to a sixth aspect of the present invention, a method for preparing the anion exchange membrane as described above is provided, comprising the following operations: S1. preparing a reaction monomer mixture containing monomer I, monomer II, and monomer III, wherein monomer I is a biphenyl monomer, monomer II is a monomer comprising a branched structure, and monomer III is a monomer comprising a nitrogen-containing heterocycle, and adding an acid catalyst to the reaction monomer mixture at a temperature of -5°C to 0°C to obtain a reaction solution; S2. allowing the reaction solution to undergo an oligomerization reaction, wherein the reaction temperature of the oligomerization reaction is 0°C to 10°C, and after the oligomerization reaction is completed, an oligomer mixture is obtained; S3. allowing the oligomer mixture to undergo an oligomerization reaction, wherein the reaction temperature of the oligomerization reaction is 0°C to 10°C, and after the oligomerization reaction is completed, an oligomer mixture is obtained; S4. allowing the oligomer mixture to undergo an oligomerization reaction, wherein the reaction temperature of the oligomerization reaction is 0°C to 10°C, and after the oligomerization reaction is completed, an oligomer mixture is obtained; S5. allowing the oligomer mixture to undergo an oligomerization reaction, wherein the reaction temperature of the oligomerization reaction is 0°C to 10°C, and the oligomer mixture is obtained; S6. allowing the oligomer mixture to undergo an oligomerization reaction, wherein the reaction temperature of the oligomerization reaction is 0°C to 10°C, and the oligomer mixture is obtained; S7. allowing the oligomer mixture to undergo an oligomerization reaction, wherein the reaction temperature of the oligomerization reaction is 0°C to 10°C, and the oligomer mixture is obtained; S8. allowing the oligomer mixture to undergo an oligomerization reaction, wherein the reaction temperature of the oligomerization reaction is 0°C to 10°C, and the oligomer mixture is obtained; S9. The mixed solution undergoes a polymerization reaction, and the reaction temperature of the polymerization reaction is 0°C to 24°C; S4. A polymer is separated from the product after the polymerization reaction is completed, and the polymer is subjected to an acid removal treatment, and the polymer is converted into a nitrogen-containing branched polymer after the acid removal treatment; S5. The nitrogen-containing branched polymer and the quaternary ammonium agent are added to the solvent B to prepare a quaternary ammonium reaction solution, and then the nitrogen-containing branched polymer and the quaternary ammonium agent are subjected to a quaternary ammonium reaction, and an anion exchange resin is separated from the product obtained by the quaternary ammonium reaction; S6. A homogeneous solution containing an anion exchange resin in the solute is prepared, and then the homogeneous solution is used to coat a film substrate,
[0089] After drying, an anion exchange membrane was obtained.
[0090] Preferably, in S1, the acid catalyst is added to the reaction monomer mixture in a dropwise manner, and the dropwise addition speed is 0.3 mL / min to 2 mL / min.
[0091] Preferably, the reaction time of the oligomerization reaction is 1 to 5 hours, and the reaction time of the polymerization reaction is 1 to 15 hours.
[0092] Preferably, the reaction temperature of the quaternization reaction is 10°C to 100°C.
[0093] Preferably, the reaction time of the quaternization reaction is 4 hours to 36 hours.
[0094] Preferably, S6 specifically includes the following operations: dissolving an anion exchange resin in solvent C, filtering the resulting mixed solution through a diaphragm, wherein the mesh size of the diaphragm is 2000 to 6000 mesh, and the filtrate filtered through the membrane is a homogeneous solution, and coating a film substrate with the homogeneous solution to obtain a semi-finished product, and drying the semi-finished product at 60°C for 8 to 12 hours.
[0095] Preferably, the solvent C is composed of at least one of dimethyl sulfoxide, tetrahydrofuran, N-methyl-2-pyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide, and acetonitrile.
[0096] According to a seventh aspect of the present invention, an electrochemical device is provided, the electrochemical device comprising the anion exchange membrane as described above. Based on the application of the anion exchange membrane provided by the present invention, the hydrogen in oxygen in the electrochemical device can be kept within a safe control range for a long time, thereby making it have good safety. In addition, the high ionic conductivity of the anion exchange membrane ensures the efficient transfer of ions inside the electrochemical device, thereby making the electrochemical device have excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0097] Figure 1 It is an ionic conductivity testing device;
[0098] Figure 2 A statistical chart of the test results of tensile strength and elongation at break measured for the test object in Test Example 1;
[0099] Figure 3 A statistical chart of the test results of ionic conductivity, water absorption rate and swelling rate measured for the test object of Test Example 1;
[0100] Figure 4 A statistical chart of test results of hydrogen content in oxygen and polarization performance of an alkaline membrane single cell of a test object of application test example 1;
[0101] Figure 5 A statistical chart of the test results of tensile strength and elongation at break measured for the test object of Test Example 2;
[0102] Figure 6 A statistical chart of the test results of ionic conductivity, water absorption rate and swelling rate measured for the test object of Test Example 2;
[0103] Figure 7 A statistical chart of the test results of the hydrogen content in oxygen and the polarization performance of the alkaline membrane single cell of the test object of the application test example 2;
[0104] Figure 8 A statistical chart of the test results of tensile strength and elongation at break measured for the test object of Test Example 3;
[0105] Fig. 9 A statistical chart of the test results of ionic conductivity, water absorption rate and swelling rate measured for the test object of Test Example 3;
[0106] Fig.10 A statistical chart of the test results of the hydrogen content in oxygen and the polarization performance of the alkaline membrane single cell of the test object of the application test example 3;
[0107] Fig.11 A statistical chart of the test results of tensile strength and elongation at break measured for the test object of Test Example 4;
[0108] Fig.12A statistical chart of the test results of ionic conductivity, water absorption rate and swelling rate measured for the test object of Test Example 4;
[0109] Fig.13 This is a statistical chart of the test results of the hydrogen content in oxygen and the polarization performance of the alkaline membrane single cell of the test object of Test Example 4. DETAILED DESCRIPTION
[0110] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.
[0111] Examples 1 to 10
[0112] The method for preparing anion exchange membranes in Examples 1 to 10 is as follows:
[0113] S1. Add 0.27 mol monomer I, 0.03 mol monomer II and 0.36 mol monomer III into 100 mL dichloromethane and mix thoroughly to obtain a reaction monomer mixture, then add an acid catalyst dropwise at 0°C at a dropping speed of 1 mL / min to the reaction monomer solution, the acid catalyst specifically comprising 22.8 mL trifluoroacetic acid and 240 mL trifluoromethanesulfonic acid, and use the solution obtained after the dropwise addition as the reaction liquid; wherein, monomer I is a biphenyl monomer, monomer II is a monomer including a branched structure, and monomer III is a monomer including a nitrogen-containing heterocycle.
[0114] S2. Keep the reaction liquid at the reaction temperature of the oligomerization reaction for 1-1.5 hours. During this process, the reaction monomers in the reaction liquid undergo oligomerization under the action of the acid catalyst. After the oligomerization reaction is completed, the product obtained is an oligomer mixture.
[0115] S3. The oligomer mixture is then heated to a polymerization reaction temperature and kept warm for 2-5.5 hours. During this process, the oligomer mixture undergoes polymerization reaction.
[0116] S4. After the reaction is completed, the polymer is discharged into pure water through an extruder, and then filtered, washed with pure water and dried. The polymer thus obtained is then dissolved in an alkaline solution for deacidification. After sufficient deacidification, the precipitate is washed and dried to obtain a nitrogen-containing branched polymer.
[0117] S5. Take 0.1 mol of the nitrogen-containing branched polymer obtained after the completion of S4 and 0.15 mol of methyl p-toluenesulfonate, add them to 200 mL of dimethyl sulfoxide, mix them thoroughly, and thus obtain a quaternization reaction solution, then heat the quaternization reaction solution to 80°C and keep it warm for 15 hours, then add ethyl acetate (2 L) to the product solution thus obtained to precipitate, then filter to obtain the precipitate precipitated from the product solution, wash the precipitate with ethyl acetate, then use 1M KBr aqueous solution (1 L) for ion exchange, and dry to obtain an anion exchange resin.
[0118] S6. The anion exchange resin is dissolved in dimethyl sulfoxide (DMSO) to obtain a homogeneous solution with a solid content of 20 wt%, and the homogeneous solution is poured onto a coating machine to obtain a semi-finished product. The semi-finished product is dried at 60°C for 8 hours, and then the dried film is immersed in 1M KOH at 60°C for 48 hours to obtain an anion exchange membrane.
[0119] In this embodiment, different experimental groups are set up by taking the material types of monomer I, monomer II and monomer III in the raw materials as variables. Based on the specific monomers I and II selected between different experimental groups, the reaction temperature and reaction time of the oligomerization reaction and the reaction temperature and reaction time of the polymerization reaction involved in S2 and S3 in the preparation of the anion exchange membrane are adaptively adjusted. The variable settings between the experimental groups are shown in Table 1. Except for the variables shown in Table 1, other experimental operations and raw material use of all experimental groups in this embodiment are strictly kept consistent.
[0120] Table 1. Examples 1 to 10 and variable settings between examples
[0121]
[0122]
[0123] The specific numbers of the anion exchange resins prepared in the above experimental groups are shown in Table 2, which shows the weight average molecular weight and polydispersity index PDI corresponding to the nitrogen-containing branched polymer obtained after step S4 in the process of preparing the anion exchange resin in each experimental group.
[0124] Table 2. Nitrogen-containing branched polymers and anion exchange resins obtained in Examples 1 to 10
[0125]
[0126]
[0127] The anion exchange resins and their corresponding chemical structures shown in Table 2 are as follows: Anion exchange resin A is
[0128]
[0129] Anion exchange resin B is
[0130]
[0131] Anion exchange resin C is
[0132]
[0133] Anion exchange resin D is
[0134]
[0135] Anion exchange resin E is
[0136]
[0137] Anion exchange resin F is
[0138]
[0139] Anion exchange resin G is
[0140]
[0141] Anion exchange resin H is
[0142]
[0143] Anion exchange resin I is
[0144]
[0145] Anion exchange resin J is
[0146]
[0147] Test Example 1
[0148] 1. Test subjects
[0149] This test example uses the anion exchange membranes prepared in Examples 1 to 10 as test objects.
[0150] 2. Test items and test methods
[0151] (1) Solubility test
[0152] The anion exchange resins were dissolved in a certain amount of dimethyl sulfoxide, and their solubility was observed at 80°C within 24 hours.
[0153] Solubility rating standard: good solubility, marked as "++"; slightly soluble, marked as "-+"; insoluble, marked as "-".
[0154] (2) Mechanical properties test
[0155] Test method:
[0156] Under constant temperature and humidity conditions of 23℃±2℃ and 50%±10% relative humidity, measure the thickness and width of the anion exchange membrane. Place the anion exchange membrane in the test fixture. When measuring the tensile strength and elongation at break, different tensile speeds can be used, which can be selected within the range of 50mm / min to 200mm / min. For each tensile speed, a separate specimen should be used. After the sample breaks, read the corresponding load value.
[0157] a. Tensile strength: The ratio of the maximum load that an anion exchange membrane can withstand when it breaks under pure tensile force to the width of the stretched membrane material. It is divided into transverse and longitudinal tensile strengths and is used to evaluate the mechanical strength of the membrane.
[0158] b. Elongation at break: The ratio of the distance between two points at break to the original length under the maximum load before the anion exchange membrane breaks. It indicates the maximum deformation that the alkaline membrane can withstand before breaking, and is used to indicate the flexibility of the anion exchange membrane.
[0159] (3) Water absorption and swelling performance test
[0160] Test method:
[0161] a. Cut the anion exchange membrane into 1cm*4cm size, put it into 1M KOH to change the base three times, and test the swelling performance in 80℃ deionized water;
[0162] b. Cut the anion exchange membrane into 5cm*5cm size, put it into 1M KOH to change the alkali three times, and test the water absorption performance in 80℃ deionized water.
[0163] (4)OH - Ionic conductivity performance (conductivity test membrane state is OH - @80℃@pure water)
[0164] Cut 10mm×45mm anion exchange membrane as a sample. Place the sample in 1M KOH aqueous solution and perform ion exchange at 80℃ for 24 hours. After completion, wash with deionized water until neutral and store in deionized water. Before testing, use a thickness gauge and a ruler to measure the thickness and width of the anion exchange membrane, respectively. Take the average value of three tests as the width a and thickness b, and take at least 3 points for each group of samples.
[0165] Ionic conductivity test equipment such as Figure 1 As shown, the four-electrode probe method is used for testing. First, lay the sample flat on the platinum wire electrode without wrinkles to ensure good contact between the sample and the platinum wire electrode, then gently place the cover and tighten the screws with a wrench. After tightening, the sample should have no protrusions, completing the assembly of the test module.
[0166] The test fixture is connected to the temperature and humidity control system. After the connection is completed, N2 (99.999%, the same below) is purged, and the flow rate on both sides is set to 500sccm. The humidification condition is set to 100% RH to ensure that the temperature of the pipeline is 5°C higher than the temperature of the test device; the actual test temperature is set according to demand. Then start the temperature and humidity device, and start the electrolysis process after the set conditions are met. Keep N2 purging throughout the process and keep the gas flow unchanged.
[0167] (5) Electrolyzed water test
[0168] The anion exchange membrane to be tested is electrolyzed by constant current method. The electrolysis current value can be adjusted within the electrolysis potential of 2V to meet the actual test needs. During the electrolysis process, the electrodes undergo electrochemical reactions, causing the carbonate (bi) ions in the anion exchange membrane to be discharged in the form of CO2 gas until all anions in the membrane are exchanged for OH- in situ. Whether the electrolysis has reached equilibrium is determined by the change in overpotential during the test process. Generally, when the electrolysis potential fluctuation value is less than 1%, it is determined that the electrolysis process is over and the system has reached equilibrium.
[0169] a.EIS test process
[0170] After electrolysis equilibrium, EIS test was performed, and the current perturbation mode was selected, the frequency range was 0.1Hz~1.0MHz, and the perturbation amplitude was 1mA to obtain the impedance spectrum. The impedance value R of the anion exchange membrane was read from the intersection of the low-frequency part of the spectrum and the real axis, and the in-plane ion conductivity of the sample was calculated according to the following formula:
[0171] σ=l / (a×b×R)
[0172] Where:
[0173] σ——is the in-plane ionic conductivity of the sample, in millisiemens per centimeter (mS / cm);
[0174] l——The distance between electrodes, in centimeters (cm);
[0175] a——the width of the film sample, in centimeters (cm);
[0176] b——the thickness of the film sample, in centimeters (cm);
[0177] R——is the measured impedance of the film sample, in ohms (Ω).
[0178] b. Polarization performance test
[0179] The polarization curve of the alkaline membrane cell was tested in the anode nickel ferrite-cathode platinum carbon catalytic system at 60℃@1M KOH.
[0180] c. Hydrogen in oxygen test
[0181] The oxygen on the anode side is tested online by GC to obtain the data of hydrogen in oxygen.
[0182] 3. Test results
[0183] The test results of this test case are recorded in Table 3 and Table 4. Figure 2 , Figure 2 The comparison of the test results of tensile strength and elongation at break of the test object in this test example is shown. Figure 3 , Figure 4 , Figure 3 The test results of ionic conductivity, water absorption and swelling rate of the test object in this test case are compared. Figure 4 The test results of the hydrogen content in oxygen and the polarization performance of the alkaline membrane single cell tested by this test are compared.
[0184] From the test results, it can be seen that the anion exchange resins prepared in Example 1 all meet the following conditions at the same time: the measured tensile strength and elongation at break both reach a high level; the measured swelling ratio is at a low level; the measured conductivity is at a high level. This shows that the anion exchange resins prepared in Example 1 all have good structural stability, electrical conductivity and anti-swelling properties at the same time. The above anion exchange resins are further applied to the electrolysis water test. Based on the above superior properties of the above anion exchange resins, the transmembrane transport of hydrogen generated during the working process of the electrolysis water system using the anion exchange resins can be suppressed. Thus, the hydrogen in the oxygen of the electrolysis water system can be controlled at a relatively low level, ensuring the working safety of the electrolysis water system. At the same time, the electrolysis water system can maintain a good ion transmission effect and ensure the electrochemical working efficiency.
[0185] By further comparing the test results of this test example, the following examples are compared with each other in terms of the selection of reaction raw materials. The difference between Example 2 and Example 7, Example 3 and Example 8, Example 4 and Example 9 is the material type of the selected monomer I. By comparison, in the above-mentioned examples for comparison, the use of p-terphenyl as the monomer I for preparing the anion exchange resin has better performance.
[0186] Table 3. Statistics of performance test results of the anion exchange resins and anion exchange membranes tested in this test case
[0187]
[0188] Table 4. Statistics of the test results of the electrolysis performance of anion exchange membranes
[0189]
[0190] Examples 11 to 16, Comparative Example 1, Comparative Example 2
[0191] Using Example 1 and Example 4 as references, and the monomer dosage ratio used in the process of preparing anion exchange membranes as variables, experiments were designed to show the influence of the dosage ratio of raw monomers on the product performance of anion resins and anion exchange membranes.
[0192] (1) Take Example 1 as a reference
[0193] Taking Example 1 as a reference, Examples 11, 12, 13 and 14 are set. The variables between the above examples are: the amount of p-terphenyl and 1,3,5-triphenylbenzene used in the process of preparing the anion exchange membrane. The amount of p-terphenyl and 1,3,5-triphenylbenzene used in each experimental group is shown in Table 5. Except for the variables shown in Table 5, the other experimental operations and raw material use of the above examples are strictly consistent with those in Example 1.
[0194] Table 5. The corresponding feeding amount of p-terphenyl and 1,3,5-triphenylbenzene in Example 1 and Example 11 to 14
[0195]
[0196]
[0197] (2) Take Example 4 as a reference
[0198] Taking Example 4 as a reference, Example 15, Example 16, Comparative Example 1 and Comparative Example 2 are set. The variables between the above examples and comparative examples are: the amount of p-terphenyl and triphenylamine used in the process of preparing the anion exchange membrane. The amounts of p-terphenyl and triphenylamine corresponding to the above examples and comparative examples are shown in Table 6. Except for the variables shown in Table 6, the other experimental operations and raw materials used in the above examples and comparative examples are strictly consistent.
[0199] Table 6. The corresponding feeding amounts of terphenyl and triphenylamine in Example 4, Example 15, Example 16, Comparative Example 1 and Comparative Example 2
[0200] Group Terphenyl feed amount / mol Triphenylamine feed amount / mol Example 4 0.27 0.03 Embodiment 15 0.285 0.015 Example 16 0.255 0.045 Comparative Example 1 0.291 0.009 Comparative Example 2 0.246 0.054
[0201] The weight average molecular weight and polydispersity index PDI of the nitrogen-containing branched polymer obtained after step S4 in the above-mentioned embodiments and comparative examples in the process of preparing anion exchange resin are shown in Table 7. For the convenience of comparison, the weight average molecular weight and polydispersity index PDI of the nitrogen-containing branched polymer obtained in Example 1 and Example 4 are also included in Table 7.
[0202] Table 7. Weight average molecular weight and PDI of nitrogen-containing branched polymers obtained in various examples and comparative examples
[0203]
[0204]
[0205] Test Example 2
[0206] 1. Test subjects
[0207] In this test example, the anion exchange membranes prepared in Examples 11 to 16, Comparative Example 1, and Comparative Example 2 were used as test objects.
[0208] 2. Test items and test methods
[0209] The test items of this test example are as follows. The test method of each test item in this test example is consistent with the test method of the corresponding test item in Test Example 1.
[0210] (1) Solubility test
[0211] (2) Mechanical properties test
[0212] a. Tensile strength
[0213] b. Elongation at break
[0214] (3) Water absorption and swelling performance test
[0215] (4)OH - Ionic conductivity performance (conductivity test membrane state is OH - @80℃@pure water)
[0216] (5) Electrolyzed water test
[0217] a.EIS test process
[0218] 3. Test results
[0219] The test results of this test case are recorded in Table 8 and Table 9. Figure 5 , Figure 5 The comparison of the test results of tensile strength and elongation at break of the test object in this test example is shown. Figure 6 , Figure 7 , Figure 6 The test results of ionic conductivity, water absorption and swelling rate of the test object in this test case are compared. Figure 7 The test results of the hydrogen content in oxygen and the polarization performance of the alkaline membrane single cell tested by this test are compared.
[0220] By comparing the test results of the test objects provided in Example 1 with those provided in Example 11, Example 12, Example 13, and Example 14, and comparing the test results of the test objects provided in Example 4 with those provided in Example 15, Example 16, Comparative Example 1, and Comparative Example 2, it can be shown that in the process of preparing anion exchange resin, the influence of the ratio of monomer I and monomer II on the product performance of anion exchange resin can be presented. Combined with the contents shown in Table 7 of this specification, it can be known that under the premise of using the same type of reaction raw materials, the ratio of monomer I and monomer II will change the weight average molecular weight and polydispersity index PDI of the nitrogen-containing branched polymer. In Examples 11 to 16, Comparative Example 1, and Comparative Example 2, the weight average molecular weight corresponding to the nitrogen-containing branched polymer obtained in Comparative Example 1 is low, lower than 40,000 g / mol, while the polydispersity index PDI corresponding to the nitrogen-containing branched polymer obtained in Comparative Example 2 is high, higher than 2.6. Further examining the test results shown in Table 8, the conductivity of the anion exchange resin prepared in Comparative Example 1 is low, while the anion exchange resin prepared in Comparative Example 2 has the problems of low tensile strength, low elongation at break, and high swelling rate, while the anion exchange resins prepared in Examples 11 to 16 can all have high tensile strength, large elongation at break, low swelling rate, and high conductivity. This shows that when the nitrogen-containing branched polymer used to prepare the anion exchange resin cannot simultaneously meet the requirements of a weight average molecular weight of not less than 40,000 g / mol and a polydispersity index PDI ≤ 2.6, the anion exchange resin cannot overcome the trade-off effect between ionic conductivity, structural stability, and water absorption and swelling characteristics.
[0221] According to the analysis of the above experimental results, the anion exchange resins prepared in Example 11, Example 12, Example 13, Example 14, Comparative Example 1, and Comparative Example 2, respectively, can have high ionic conductivity, good structural stability, and low water absorption and swelling properties. On this basis, the test results of the above experimental groups were compared with the experimental groups of Example 1, which were used as references. It can be seen that in the process of preparing the anion exchange resin, the molar ratio of monomer I and monomer II is controlled at monomer I: monomer II = 85-95: 5-15, thereby making it easier to obtain a nitrogen-containing branched polymer that simultaneously satisfies the weight average molecular weight of not less than 40,000 g / mol and the polydispersity index PDI ≤ 2.6.
[0222] Table 8. Statistics of performance test results of the anion exchange resins and anion exchange membranes tested in this test case
[0223]
[0224]
[0225] Table 9. Statistics of the test results of the electrolysis performance of anion exchange membranes
[0226]
[0227] Example 17, Comparative Examples 3 to 6
[0228] In this example, Example 1, Example 2, Example 3, Example 4, and Example 5 are used as controls, and anion exchange membranes are prepared according to the examples and comparative examples. The types of monomers I and II used to prepare anion exchange membranes are the same between the corresponding experimental groups. The control conditions of each experimental group and the specific method used to prepare anion exchange membranes are specifically described below.
[0229] (1) Embodiment 17
[0230] Taking Example 1 as a reference, the method for preparing an anion exchange membrane in Example 17 is as follows:
[0231] S1. Dissolve 0.27mmol of p-terphenyl, 0.03mmol of 1,3,5-triphenylbenzene and 0.36mol of 3-quinuclidine hydrochloride in 100mL of dichloromethane, stir at 0°C, and slowly drop 240mL of trifluoromethanesulfonic acid and 22.8mL of trifluoroacetic acid. After the dropwise addition is completed, continue stirring for 72 hours to obtain a viscous solution. Wash the viscous solution with pure water, 1mol NaOH aqueous solution and pure water in turn, and dry at 100°C for 30 hours to obtain a nitrogen-containing branched polymer in the form of a light yellow powder.
[0232] S2. 0.1 mol of the nitrogen-containing branched polymer and 0.15 mol of iodomethane were dissolved in dimethyl sulfoxide, and the mixture was stirred at 60°C for 10 hours. After the reaction was completed, the obtained product was washed three times with pure water and dried at 100°C for 30 hours to obtain a light yellow powdered anion exchange resin.
[0233] S3. The anion exchange resin is dissolved in N,N-dimethylacetamide to obtain a polymer solution, the polymer solution is coated on a glass plate, dried in an oven at 80°C for 5 hours, and then heated to 120°C and dried for another 20 hours to obtain an iodine ion exchange membrane.
[0234] S4. Under room temperature, the iodine ion exchange membrane was immersed in a 1M NaOH aqueous solution for 5 hours. The membrane was taken out and washed with pure water, and dried in an oven at 100°C under nitrogen protection for 5 hours to obtain an anion exchange membrane.
[0235] (2) Comparative Example 3
[0236] Taking Example 2 as a reference, the method for preparing an anion exchange membrane in Comparative Example 3 is as follows:
[0237] S1. 0.27 mol of terphenyl, 0.03 mmol of triptycene and 0.36 mol of 3-quininone were added to 100 mL of dichloromethane, and stirred for 10 minutes with a magnetic stirrer in an ice-water bath and air atmosphere to obtain a light yellow mixed solution. Then 240 mL of trifluoromethanesulfonic anhydride (TFSA) was added dropwise to the white mixed solution. After the addition was complete, the mixture was stirred and reacted for 36 hours. The obtained viscous solution was poured into a 200 mL+200 mL mixed solution of water and methanol to precipitate a yellow polymer. The yellow polymer was crushed and collected by filtration, and washed with a 1 M K2CO3 solution at room temperature for 12 hours to neutralize the acid remaining in the reaction, and then washed three times with deionized water, and dried in a vacuum oven at 80°C for 12 hours to obtain a nitrogen-containing branched polymer.
[0238] S2. Dissolve 0.1 mol of the polymer obtained in S1 in 30 mL of DMSO, stir at room temperature for 30 minutes, then add K2CO3 and 0.15 mol of iodomethane, stir at room temperature in the dark for 12 hours, then heat to 60°C and stir for 6 hours, add 200 mL of ether to the obtained viscous solution, filter the yellow precipitate, rinse with deionized water 3 times, and dry in a vacuum oven at 80°C for 12 hours to obtain an anion exchange resin.
[0239] S3. The anion exchange resin obtained in S2 was dissolved in 15 mL of DMSO. The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter, cast on a glass plate, and then dried on a solvent evaporation heating table at 120°C for 6 hours. After completely removing the residual solvent, a 40 μm thick I-type polymer membrane was obtained.
[0240] S4. The I-type polymer membrane was immersed in a 1 M KOH solution to obtain an OH-type membrane, which was then washed with deionized water for three times to finally obtain an anion exchange membrane.
[0241] (3) Comparative Example 4
[0242] Taking Example 3 as a reference, the method for preparing an anion exchange membrane in Comparative Example 4 is as follows:
[0243] S3. 0.27 mol of p-terphenyl, 0.03 mol of triphenylmethane and 0.36 mol of 1-methyl-4-piperidinecarboxaldehyde were added to 100 mL of dichloromethane, and stirred for 10 min with a magnetic stirrer in an ice-water bath and air atmosphere to obtain a light yellow mixed solution. Then 240 mL of TFSA was added dropwise to the above white mixed solution. After the addition was complete, the mixture was stirred and reacted for 1 hour. The obtained viscous solution was poured into a 200 mL+200 mL mixed solution of water and methanol to precipitate a light yellow polymer. The above yellow polymer was crushed, and the fragments were collected by filtration, and washed with a 1M K2CO3 solution at room temperature for 12 hours to neutralize the residual acid in the reaction, and then washed three times with deionized water, and dried in a vacuum oven at 80°C for 12 hours to obtain a nitrogen-containing branched polymer.
[0244] S2. Dissolve 0.1 mol of nitrogen-containing branched polymer in DMSO, stir at room temperature for 30 minutes, then add K2CO3 and 0.15 mol of iodomethane, stir in the dark at room temperature for 12 hours, then heat to 60°C and stir for 6 hours, add 200 mL of ether to the obtained viscous solution, filter the yellow precipitate, rinse with deionized water 3 times, and dry in a vacuum oven at 80°C for 12 hours to obtain anionic resin.
[0245] S3. The anion resin (0.4 g) was dissolved in 15 mL DMSO, the polymer solution was filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter, cast on a glass plate, and then dried on a solvent evaporation heating table at 120°C for 6 hours to obtain a 40 μm thick I-type polymer membrane after completely removing the residual solvent; the I-type polymer membrane was immersed in a 1 M KOH solution, ion exchanged at 60°C for 12 hours to obtain an OH-type membrane, and then washed with deionized water 3 times to finally obtain an anion exchange membrane.
[0246] (4) Comparative Example 5
[0247] Taking Example 4 as a reference, the method for preparing an anion exchange membrane in Comparative Example 5 is as follows:
[0248] S1. Add 0.27 mol of p-terphenyl into a 250 mL three-necked flask, then add 100 mL of dichloromethane solution, followed by 0.36 mol of N-methyl-4-piperidone and 0.03 mol of triphenylamine. After mechanical stirring for a period of time, slowly add 22.8 mL of trifluoroacetic acid and 240 mL of trifluoromethanesulfonic acid under ice bath conditions. Maintain ice bath conditions during the reaction. The reaction takes 4 hours. When the solution becomes highly viscous, pour the reaction solution into methanol to precipitate the crude polymer, then wash with deionized water until neutral, and dry at 60°C for 24 hours to obtain a nitrogen-containing branched polymer.
[0249] S2. Weigh 0.1 mol of nitrogen-containing branched polymer and add 200 mL of dimethyl sulfoxide. After dissolving, add potassium carbonate and 0.15 mol of iodomethane. React in the dark at room temperature for about 36 hours. After the reaction, pour the resulting solution into ethyl acetate to precipitate a solid powdery product. After filtering and drying, wash with deionized water several times to remove unreacted salts, and dry at 60°C for 24 hours to obtain an anion exchange resin.
[0250] S3. Weigh 0.05 g of anion exchange resin and dissolve it in 5 mL of dimethyl sulfoxide. Centrifuge the casting solution and cast it into a glass mold. Dry it at 60°C for 24 hours to obtain a polymer membrane. Soak the polymer membrane in 1 mol / L NaOH solution at room temperature for 24 hours, then wash it repeatedly with deionized water and soak it for 24 hours until it becomes neutral to obtain an anion exchange membrane.
[0251] (5) Comparative Example 6
[0252] Taking Example 5 as a reference, the method for preparing an anion exchange membrane in Comparative Example 6 is as follows:
[0253] S1. Add 0.27 mol of p-terphenyl, 0.03 mol of 9,9-spirobifluorene and 0.36 mol of 1-methyl-4-piperidinecarboxaldehyde into 100 mL of dichloromethane, stir with a magnetic stirrer in an ice-water bath and air atmosphere for 10 minutes to obtain a light yellow mixed solution, then add 240 mL of TFSA dropwise to the above white mixed solution, stir and react for 1 hour after the addition, pour the obtained viscous solution into 200 mL+200 mL of a mixed solution of water and methanol to precipitate a light yellow polymer; crush the above yellow polymer, collect the fragments by filtration, wash with a 1M K2CO3 solution at room temperature for 12 hours with stirring to neutralize the residual acid in the reaction, then wash three times with deionized water, and dry in a vacuum oven at 80°C for 12 hours to obtain a nitrogen-containing branched polymer.
[0254] S2. Dissolve 0.1 mol of nitrogen-containing branched polymer in DMSO, stir at room temperature for 30 minutes, then add K2CO3 and 0.15 mol of iodomethane, stir at room temperature in the dark for 12 hours, then heat to 60°C and stir for 6 hours, add 200 mL of ether to the obtained viscous solution, filter the yellow precipitate, rinse with deionized water 3 times, and dry in a vacuum oven at 80°C for 12 hours to obtain a quaternary ammonium branched anion exchange resin.
[0255] S3. The anion exchange resin (0.4 g) was dissolved in DMSO (15 mL), the polymer solution was filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter, cast on a glass plate, and then dried on a solvent volatilization heating table at 120°C for 6 hours; after completely removing the residual solvent, a 40 μm thick I-type polymer membrane was obtained; the I-type polymer membrane was immersed in a 1 M KOH solution, ion exchanged at 60°C for 12 hours to obtain an OH-type membrane, and then washed with deionized water 3 times to finally obtain an anion exchange membrane.
[0256] The weight average molecular weight and polydispersity index PDI of the nitrogen-containing branched polymers obtained in the process of preparing anion exchange resins in Example 17 and Comparative Examples 3 to 6 are shown in Table 10. Referring to the settings of Example 17 and Comparative Examples 3 to 6, it can be seen that the specific experimental groups in Example 1 are used as references, and different synthesis methods are used to prepare nitrogen-containing branched polymers under the condition that the same monomers I and II are used as in Example 1 as a reference. Comparing the data shown in Table 10 with the data shown in Table 2, it can be seen that the different preparation methods can significantly change the weight average molecular weight and polydispersity index PDI of the nitrogen-containing branched polymers. Among them, although the obtained Comparative Examples 3 to 6 can produce nitrogen-containing branched polymers with suitable weight average molecular weights, the polydispersity index PDI of the nitrogen-containing branched polymers is as high as 2.6 or more.
[0257] Table 10. Weight average molecular weight and PDI of nitrogen-containing branched polymers obtained in Example 17 and Comparative Examples 3 to 6
[0258]
[0259] Test Example 3
[0260] 1. Test subjects
[0261] This test example uses the anion exchange membranes prepared in Example 17 and Comparative Examples 3 to 6 as test objects.
[0262] 2. Test items and test methods
[0263] The test items of this test example are as follows. The test method of each test item in this test example is consistent with the test method of the corresponding test item in Test Example 1.
[0264] (1) Solubility test
[0265] (2) Mechanical properties test
[0266] a. Tensile strength
[0267] b. Elongation at break
[0268] (3) Water absorption and swelling performance test
[0269] (4)OH - Ionic conductivity performance (conductivity test membrane state is OH - @80℃@pure water)
[0270] (5) Electrolyzed water test
[0271] a.EIS test process
[0272] b. Polarization performance test
[0273] c. Hydrogen in oxygen test
[0274] 3. Test results
[0275] The test results of this test case are recorded in Table 11 and Table 12. Figure 8 , Figure 8 The comparison of the test results of tensile strength and elongation at break of the test object in this test example is shown. Fig. 9 , Fig.10 , Fig. 9 The test results of ionic conductivity, water absorption and swelling rate of the test object in this test case are compared. Fig.10 The test results of the hydrogen content in oxygen and the polarization performance of the alkaline membrane single cell tested by this test are compared.
[0276] As described above, when the types of monomer raw materials used to prepare nitrogen-containing branched polymers are the same, the preparation method will affect the weight average molecular weight and polydispersity PDI of the nitrogen-containing branched polymers. The test results of this test example show that among the test objects of this test example, the anion exchange resin provided by Example 17 can have both high ion conductivity, good structural stability and low water absorption and swelling characteristics, and its comprehensive performance is significantly better than the anion exchange resins prepared in Comparative Examples 3 to 6. However, when the anion exchange resin of Example 17 is compared with the anion exchange resin prepared in Example 1, the anion exchange resin prepared in Example 1 has better comprehensive performance.
[0277] Table 11. Statistics of performance test results of the anion exchange resins and anion exchange membranes tested in this test case
[0278]
[0279]
[0280] Table 12. Statistics of the test results of the electrolysis performance of anion exchange membranes
[0281]
[0282] Examples 18 to 21, Comparative Example 7, Comparative Example 8
[0283] Taking Example 1 as a reference, Examples 18, 19, 20, 21, Comparative Examples 7 and 8 were set up, and the acid catalyst used in the preparation of anion exchange membranes was used as a variable to design experiments to show the influence of the use of acid catalysts on the product performance of anion resins and anion exchange membranes.
[0284] The variables between Examples 18 to 21, Comparative Example 7, and Comparative Example 8 are: the type and amount of the acid catalyst in the process of preparing the anion exchange membrane. The acid catalyst used in the above examples and comparative examples in the process of preparing the anion exchange membrane is shown in Table 13, wherein the acid catalysts used in Example 1, Example 18, Example 19, Comparative Example 7, and Comparative Example 8 are all compounded with trifluoroacetic acid and trifluoromethanesulfonic acid according to a volume ratio of trifluoroacetic acid: trifluoromethanesulfonic acid = 22.8:240, and the acid catalyst used in Example 20 is trifluoroacetic acid, and the acid catalyst used in Example 21 is trifluoromethanesulfonic acid. The equivalent amount of the acid catalyst used shown in Table 13 is based on the amount of monomer III as an equivalent reference.
[0285] Except for the variables shown in Table 13, other experimental operations and raw material usage of Examples 18 to 21, Comparative Example 7 and Comparative Example 8 are strictly consistent with those of Example 1.
[0286] Table 13. Acid catalyst usage corresponding to Examples 18 to 21, Comparative Example 7, and Comparative Example 8
[0287]
[0288] The weight average molecular weight and polydispersity index PDI of the nitrogen-containing branched polymer obtained after step S4 is completed in the process of preparing anion exchange resin in Examples 18 to 21, Comparative Examples 7 and Comparative Examples 8 are shown in Table 14. For the convenience of comparison, the weight average molecular weight and polydispersity index PDI of the nitrogen-containing branched polymer obtained in Example 1 are also recorded in Table 14. Among them, in the process of preparing the nitrogen-containing branched polymer in Comparative Example 7, the polymerization reaction failed, resulting in the molecular weight of the obtained nitrogen-containing branched polymer being too low, and in the process of preparing the nitrogen-containing branched polymer in Comparative Example 8, there was a situation of violent polymerization during polymerization, resulting in the molecular weight of the obtained nitrogen-containing branched polymer being non-uniform. From the situation of preparing the nitrogen-containing branched polymer in Example 1, Example 18, Example 19, Example 20 and Example 21, it can be known that the use of any one of trifluoroacetic acid and trifluoromethanesulfonic acid or a combination of the two as the acid catalyst for preparing the nitrogen-containing branched polymer can successfully catalyze the polymerization reaction of the raw monomers and successfully prepare the nitrogen-containing branched polymer.
[0289] Table 14. Weight average molecular weight and PDI of nitrogen-containing branched polymers obtained in Examples 18 to 21, Comparative Example 7, and Comparative Example 8
[0290]
[0291]
[0292] Note: “ / ” indicates that the polymerization reaction for preparing nitrogen-containing branched polymer failed and no membrane performance data was available, or the explosion resulted in uneven molecular weight and insoluble polymer, so no membrane performance data could be obtained.
[0293] Test Example 4
[0294] 1. Test subjects
[0295] This test example uses the anion exchange membranes prepared in Examples 18 to 21, Comparative Example 7, and Comparative Example 8 as test objects.
[0296] 2. Test items and test methods
[0297] The test items of this test example are as follows. The test method of each test item in this test example is consistent with the test method of the corresponding test item in Test Example 1.
[0298] (1) Solubility test
[0299] (2) Mechanical properties test
[0300] a. Tensile strength
[0301] b. Elongation at break
[0302] (3) Water absorption and swelling performance test
[0303] (4)OH - Ionic conductivity performance (conductivity test membrane state is OH - @80℃@pure water)
[0304] (5) Electrolyzed water test
[0305] a.EIS test process
[0306] b. Polarization performance test
[0307] c. Hydrogen in oxygen test
[0308] 3. Test results
[0309] The test results of this test case are recorded in Table 15 and Table 16. Fig.11 , Fig.11The comparison of the test results of tensile strength and elongation at break of the test object in this test example is shown. Fig.12 , Fig.13 , Fig.12 The test results of ionic conductivity, water absorption and swelling rate of the test object in this test case are compared. Fig.13 The test results of the hydrogen content in oxygen and the polarization performance of the alkaline membrane single cell tested by this test are compared.
[0310] The anion exchange resins provided in Comparative Examples 7 and 8 are not dissolved, so the corresponding product performance of the test objects provided in Comparative Examples 7 and 8 cannot be measured. Except for Comparative Examples 7 and 8, the remaining test objects in this test example all have good comprehensive performance. Among them, the equivalent of the acid catalyst used in the polymerization reaction of preparing nitrogen-containing branched polymers in Example 1, Example 20, and Example 21 is the same. Under this condition, the product performance corresponding to the anion exchange resin and anion exchange membrane prepared in Example 1 shows obvious comprehensive advantages, which shows that compared with using any one of trifluoroacetic acid and trifluoromethanesulfonic acid as an acid catalyst for preparing nitrogen-containing branched polymers, the combination of trifluoroacetic acid and trifluoromethanesulfonic acid as an acid catalyst for preparing nitrogen-containing branched polymers can play a synergistic role, so that the comprehensive performance of the anion exchange resin and anion exchange membrane prepared subsequently is further improved.
[0311] Table 15. Statistics of performance test results of the anion exchange resins and anion exchange membranes tested in this test case
[0312]
[0313] Note: “ / ” indicates that the polymerization reaction for preparing nitrogen-containing branched polymer failed and no membrane performance data was available, or the explosion resulted in uneven molecular weight and insoluble polymer, so no membrane performance data could be obtained.
[0314] Table 16. Statistics of the test results of the electrolysis performance of anion exchange membranes
[0315]
[0316]
[0317] Note: “ / ” indicates that the polymerization reaction for preparing nitrogen-containing branched polymer failed and no membrane performance data was available, or the explosion resulted in uneven molecular weight and insoluble polymer, so no membrane performance data could be obtained.
[0318] Embodiment 22, 23
[0319] In Example 22 and Example 23, an anion exchange membrane was prepared by referring to the method for preparing an anion exchange membrane in Example 1. The difference from Example 1 is that in Example 22 and Example 23, the material types of monomer I, monomer II and monomer III in the raw materials were replaced in the process of preparing the anion exchange membrane. Based on the selected specific monomer I and monomer II, the reaction temperature and reaction time of the oligomerization reaction involved in S2 and S3 in the preparation of the anion exchange membrane, and the reaction temperature and reaction time of the polymerization reaction were adaptively adjusted, as shown in Table 17. In addition to the above differences, other experimental operations and raw material use of Example 22 and Example 23 are strictly consistent with Example 1.
[0320] Table 17. Experimental groups set in Example 22 and Example 23 and variable settings between groups
[0321]
[0322] The anion exchange resin prepared in the process of preparing anion exchange membrane in Example 22 is marked as anion exchange resin K, and the anion exchange resin prepared in the process of preparing anion exchange membrane in Example 23 is marked as anion exchange resin L.
[0323] Anion exchange resin K is
[0324]
[0325] Anion exchange resin L is
[0326]
[0327] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A nitrogen-containing branched polymer, characterized in that: The molecular structure of the nitrogen-containing branched polymer includes a nitrogen-containing heterocycle, a branching structure and a biphenyl group, the number of branching points of each branching structure is not less than 3, and the biphenyl group is connected to the branching site of the branching structure through the nitrogen-containing heterocycle; A represents the molar proportion of the biphenyl group in the nitrogen-containing branched polymer, and B represents the molar proportion of the branched structure in the nitrogen-containing branched polymer, A:B=80-99:1-20; the polydispersity index PDI of the nitrogen-containing branched polymer is ≤2.6, and the weight average molecular weight of the nitrogen-containing branched polymer is 40000 g / mol to 500000 g / mol.
2. The nitrogen-containing branched polymer according to claim 1, characterized in that: The biphenyl group includes at least one of a diphenyl group, a terphenyl group, and a quaterphenyl group.
3. The nitrogen-containing branched polymer according to claim 1, characterized in that: The branched structure includes a benzene ring structure provided with branching sites.
4. The nitrogen-containing branched polymer as claimed in claim 3, characterized in that: The branched structure includes at least one of the following structures: a 1,3,5-triphenylbenzene structural unit, a triphenylmethane structural unit, a 9,10-triphenylene structural unit, a tetraphenylmethane structural unit, a triptycene structural unit, a 9,9'-diphenylfluorene structural unit, a 9,9'-spirobifluorene structural unit, a 9,9'-bifluorene structural unit, a 9,9'-bicarbazole structural unit, a 4,4-di(9-carbazole)biphenyl structural unit, a 2,2'-bi-9,9'-spirobi[9H-fluorene] structural unit, and a triphenylamine structural unit.
5. The nitrogen-containing branched polymer according to claim 1, characterized in that: The nitrogen-containing heterocyclic ring includes at least one of a piperidine ring and a quinuclidine ring.
6. The nitrogen-containing branched polymer according to claim 1, characterized in that: The molecular structure of the nitrogen-containing branched polymer includes segment I and segment II; The general structural formula of the segment I is Wherein, A represents the nitrogen-containing heterocycle, Ar1 represents the biphenyl group, and X represents the degree of polymerization of the segment I; The segment II is composed of the nitrogen-containing heterocycle and the branched structure. In the segment II, the nitrogen-containing heterocycle is directly connected to the branching site of the branched structure.
7. The nitrogen-containing branched polymer according to claim 6, characterized in that: The nitrogen-containing branched polymer includes a basic structural unit formed by connecting the segment I and the segment II; In the basic structural unit, the connection mode of the segment I and the segment II is: the biphenyl group in the segment I is connected to the nitrogen-containing heterocycle in the segment II.
8. The nitrogen-containing branched polymer according to claim 7, characterized in that: In the basic structural unit, the number of the segments I directly connected to each segment II is ≥3.
9. The nitrogen-containing branched polymer according to claim 1, characterized in that: The weight average molecular weight of the nitrogen-containing branched polymer is 40000 g / mol to 250000 g / mol.
10. The nitrogen-containing branched polymer according to claim 1, characterized in that: The biphenyl group is a terphenyl group.
11. The nitrogen-containing branched polymer according to claim 10, characterized in that: The nitrogen-containing polymer includes at least one of nitrogen-containing branched polymer A, nitrogen-containing branched polymer B, nitrogen-containing branched polymer C, nitrogen-containing branched polymer D, and nitrogen-containing branched polymer E; The nitrogen-containing branched polymer A is The nitrogen-containing branched polymer B is The nitrogen-containing branched polymer C is The nitrogen-containing branched polymer D is The nitrogen-containing branched polymer E is 12. The method for preparing a nitrogen-containing branched polymer according to any one of claims 1 to 11, characterized in that: The following operations are included: S1. preparing a reaction monomer mixture containing monomer I, monomer II, and monomer III, wherein the monomer I is a biphenyl monomer, the monomer II is a monomer including the branched structure, and the monomer III is a monomer including a nitrogen-containing heterocyclic ring, and adding an acid catalyst to the reaction monomer mixture at a temperature of -5°C to 0°C to obtain a reaction solution; S2. allowing the reaction solution to undergo an oligomerization reaction, wherein the reaction temperature of the oligomerization reaction is 0°C to 10°C, and after the oligomerization reaction is completed, an oligomer mixture is obtained; S3. allowing the oligomer mixture to undergo a polymerization reaction, wherein the reaction temperature of the polymerization reaction is 0°C to 24°C; S4. Separating a polymer from the product after the polymerization reaction is completed, and performing an acid removal treatment on the polymer, wherein the polymer is converted into the nitrogen-containing branched polymer after the acid removal treatment.
13. An anion exchange resin, characterized in that: The anion dendritic exchange resin comprises a quaternary ammonium product of the nitrogen-containing branched polymer according to any one of claims 1 to 11.
14. The method for preparing an anion exchange resin according to claim 13, characterized in that: The following operations are included: S1. preparing a reaction monomer mixture containing monomer I, monomer II, and monomer III, wherein the monomer I is a biphenyl monomer, the monomer II is a monomer including the branched structure, and the monomer III is a monomer including a nitrogen-containing heterocyclic ring, and adding an acid catalyst to the reaction monomer mixture at a temperature of -5°C to 0°C to obtain a reaction solution; S2. allowing the reaction solution to undergo an oligomerization reaction, wherein the reaction temperature of the oligomerization reaction is 0°C to 10°C, and after the oligomerization reaction is completed, an oligomer mixture is obtained; S3. allowing the oligomer mixture to undergo a polymerization reaction, wherein the reaction temperature of the polymerization reaction is 0°C to 24°C; S4. separating the polymer from the product after the polymerization reaction, and subjecting the polymer to an acid-free treatment, wherein the polymer is converted into the nitrogen-containing branched polymer after the acid-free treatment; S5. Adding the nitrogen-containing branched polymer and the quaternizing agent into solvent B to prepare a quaternization reaction solution, and then subjecting the nitrogen-containing branched polymer and the quaternizing agent to a quaternization reaction, and separating the anion exchange resin from the product obtained by the quaternization reaction.
15. The method for preparing an anion exchange resin according to claim 14, characterized in that: The monomer I comprises at least one of the following biphenyl monomers:
16. The method for preparing an anion exchange resin according to claim 14, characterized in that: The monomer II comprises at least one of the following materials:
17. The method for preparing an anion exchange resin according to claim 14, characterized in that: The monomer III includes at least one of a piperidone monomer and a quinuclidinone monomer.
18. The method for preparing an anion exchange resin according to claim 17, characterized in that: The piperidone monomer comprises at least one of the following materials: The quinuclidine monomer comprises at least one of the following materials:
19. The method for preparing an anion exchange resin according to claim 14, characterized in that: The acid catalyst includes at least one of methanesulfonic acid, pentafluoropropionic acid, trifluoroacetic acid, trifluoromethanesulfonic acid, and heptafluorobutyric acid. Taking the feeding amount of the monomer III as an equivalent reference, the feeding amount of the acid catalyst satisfies 4 to 14 eq.
20. The method for preparing an anion exchange resin according to claim 14, characterized in that: The quaternizing agent includes at least one of methyl trifluoroacetate, methyl p-toluenesulfonate, iodomethane, propyl bromide, ethyl iodide, propyl iodide, butyl iodide, pentyl iodide, hexyl iodide, ethyl bromide, butyl bromide, pentyl bromide, hexyl bromide, cyclohexyl bromide, cyclopentyl bromide, cyclohexyl bromide, methyl methanesulfonate, ethyl methanesulfonate, propyl methanesulfonate, butyl methanesulfonate, propyl ethanesulfonate, ethyl ethanesulfonate, but-3-yn-1-yl methanesulfonate, allyl allyl sulfonate, methyl benzenesulfonate, methyl nitrobenzenesulfonate, methyl trifluoromethanesulfonate, ethyl trifluoromethanesulfonate, ethyl toluenesulfonate, toluene-4-sulfonic acid cyclobutyl ester, butyl toluenesulfonate, neopentylbenzenesulfonate, tetrahydro-2H-pyran-4-yl methanesulfonate, or cyclohexyl p-toluenesulfonate.
21. The method for preparing an anion exchange resin according to claim 14, characterized in that: The preparation of the reaction monomer mixture includes the following operations: mixing the monomer I, the monomer II, and the monomer III in a solvent A, wherein the solvent A is composed of at least one of dichloromethane, chloroform, chloroform, or tetrahydrofuran.
22. The method for preparing an anion exchange resin according to claim 14, characterized in that: The reaction temperature of the quaternization reaction is 10°C to 100°C.
23. The method for preparing an anion exchange resin according to claim 14, characterized in that: The solvent B is composed of at least one of dimethyl sulfoxide, tetrahydrofuran, N-methyl-2-pyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide and acetonitrile.
24. The method for preparing an anion exchange resin according to claim 14, characterized in that: In S5, separating the anion exchange resin from the product obtained by the quaternization reaction specifically includes the following operations: adding a precipitant to the product obtained by the quaternization reaction, washing and drying the precipitate precipitated from the product to obtain the anion exchange resin; The precipitant includes at least one of ethanol, ethyl acetate, ethylene glycol, ethyl ether, tetrahydrofuran, acetone or water.
25. An anion exchange membrane, characterized in that: The anion exchange membrane comprises the anion exchange resin as claimed in claim 13.
26. The method for preparing an anion exchange membrane according to claim 25, characterized in that: The following operations are included: S1. preparing a reaction monomer mixture containing monomer I, monomer II, and monomer III, wherein the monomer I is a biphenyl monomer, the monomer II is a monomer including the branched structure, and the monomer III is a monomer including a nitrogen-containing heterocyclic ring, and adding an acid catalyst to the reaction monomer mixture at a temperature of -5°C to 0°C to obtain a reaction solution; S2. allowing the reaction solution to undergo an oligomerization reaction, wherein the reaction temperature of the oligomerization reaction is 0°C to 10°C, and after the oligomerization reaction is completed, an oligomer mixture is obtained; S3. allowing the oligomer mixture to undergo a polymerization reaction, wherein the reaction temperature of the polymerization reaction is 0°C to 24°C; S4. separating the polymer from the product after the polymerization reaction, and subjecting the polymer to an acid-free treatment, wherein the polymer is converted into the nitrogen-containing branched polymer after the acid-free treatment; S5. The nitrogen-containing branched polymer and the quaternizing agent are added to the solvent B to prepare a quaternization reaction solution, and then the nitrogen-containing branched polymer and the quaternizing agent are subjected to a quaternization reaction, and the anion exchange resin is separated from the product obtained by the quaternization reaction; S6. preparing a homogeneous solution containing the anion exchange resin in the solute, and then coating a film substrate with the homogeneous solution, and drying to obtain the anion exchange membrane.
27. An electrochemical device, characterized in that: The electrochemical device comprises the anion exchange membrane as claimed in claim 25.
Citation Information
Cited By
Branched agglomerated aryl cyclamine anion exchange membrane containing multiple cationic groups as well as preparation method and application of branched agglomerated aryl cyclamine anion exchange membrane
CN120900451A
Branched polyaromatic piperidine anion exchange membrane, preparation method and application
CN120944045A
Multi-branched polymer, preparation method thereof, anion exchange membrane and alkaline electrolysis device
CN121824868A